Analisis Effect Size Pengaruh Bahan Ajar IPA Bermuatan Literasi Sains Terhadap Hasil Belajar Siswa SMP/MTs - Silvia Agustin*; Asrizal Asrizal; Festiyed Festiyed (Universitas Syiah Kuala, 2021)
The 21st century is the century where science literacy into focus on science education or science. The results of the test PISA the year 2018 showed that the literacy skills of students in Indonesia are still low. The average scientific literacy of Indonesian students is 396 and still below the score specified by the OECD 489. Compared to other countries, Indonesia ranked no 9 from the bottom to the aspects of assessment science. The purpose of this study was to determine the magnitude of the influence of the teaching materials of integrated IPA learning outcomes and the improvement of scientific literacy of students in SMP/MTs. This study used the effect size analysis method that studied 20 articles. Based on the results of the research that has been done can be known as 1) the use of integrated science teaching materials with literacy has a significant effect on the aspects of the theme, especially on the theme of motion in everyday life with an effect size of 4,41 in the high category, 2) the use of integrated science teaching materials with literacy has a more effective effect on Grade VIII level aspects with an effect size of 1.80 high categories, and 3) integrated science teaching materials with literacy have a significant effect on aspects of learning outcomes, especially knowledge aspects with an effect size of 1.80 high categories